The relationship between physical education teachers’ relatedness support and students’ psychological needs and study motivation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The role of teachers in developing autonomy, competence, and relatedness in students is well established. This study investigated the correlations between students’ perception of relatedness support and their levels of psychological needs satisfaction and study motivation in physical education classes. Questionnaire data were gathered from 149 students (aged 14 to 16, 137 boys, 151 girls). Using 5-point rating scales, the questionnaires measured 1) teachers’ relatedness support behaviors, 2) students’ levels of satisfaction autonomy, competence, and relatedness satisfaction, and 3) students’ motivation to learn in physical education classes. A descriptive statistical analysis, reliability analysis, and correlation analysis were performed on the measured variables, and a path analysis was performed to verify the relationship between each variable. The bootstrap method determined the impact of teachers’ relatedness on psychological needs and internal motivation. Teacher’s relatedness support and students’ basic psychological needs and learning motivation showed a significant positive correlation (p < 0.01). Relatedness support had a significant effect on autonomy (β = 1.21, p < 0.001), relatedness (β = 0.77, p < 0.001), and competence (β= 1.02, p < .001). The three psychological needs had a significant effect on learning motivation (autonomy: β = 0.37, p < 0.001; relatedness: β = 0.41, p < 0.001; competence: β = 0.46, p < 0.001). Relatedness support did not have a significant effect on learning motivation (β = -0.33, p > 0.05). These findings demonstrate the importance of relatedness support teaching behaviors in physical education classes. Future research must aim to enhance these behaviors.